2004
DOI: 10.1007/s11916-996-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia as a sympathetically maintained pain syndrome

Abstract: Abnormal activity of the sympathetic nervous system may be involved in the pathogenesis of chronic pain syndromes. This article reviews the animal studies of sympathetically induced pain behavior, the controversy of sympathetically maintained pain in clinical practice, and the dysautonomic nature of fibromyalgia (FM). FM has neuropathic pain features (stimuli-independent pain state accompanied by allodynia and paresthesias). The proposal of FM as a sympathetically maintained pain syndrome is based on the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 23 publications
12
91
1
3
Order By: Relevance
“…Preliminary evidence supports the hypothesis that autonomic dysfunction, characterized by a high baseline state of sympathetic arousal and decreased parasympathetic activity resulting in a blunted sympathetic response to stressors, is a potential pathogenic mechanism in FM (Clauw & Chrousos, 1997;Martinez-Lavin, 2004). Tilt table testing has revealed that patients with FM may have neurally mediated hypotension, a form of autonomic dysfunction (Bou-Holaigah, Rowe, Kan, & Calkins, 1995;Raj, Brouillard, Simpson, Hopman, & Abdollah, 2000), suggesting poor modulation of parasympathetic reactivity.…”
Section: Fibromyalgia and Autonomic Dysfunctionmentioning
confidence: 70%
“…Preliminary evidence supports the hypothesis that autonomic dysfunction, characterized by a high baseline state of sympathetic arousal and decreased parasympathetic activity resulting in a blunted sympathetic response to stressors, is a potential pathogenic mechanism in FM (Clauw & Chrousos, 1997;Martinez-Lavin, 2004). Tilt table testing has revealed that patients with FM may have neurally mediated hypotension, a form of autonomic dysfunction (Bou-Holaigah, Rowe, Kan, & Calkins, 1995;Raj, Brouillard, Simpson, Hopman, & Abdollah, 2000), suggesting poor modulation of parasympathetic reactivity.…”
Section: Fibromyalgia and Autonomic Dysfunctionmentioning
confidence: 70%
“…Patients with FM have changes consistent with ongoing sympathetic hyperactivity and that FM pain is submissive to sympathetic blockade and is rekindled by norepinephrine injections [46]. Recent studies in animals and humans further confirm the role of sympathetic hyperactivity in inducing mechanical hyperalgesia and allodynia.…”
Section: Active Myofascial Trigger Points Contribute To Sympathetic Hmentioning
confidence: 91%
“…Esses pacientes apresentam padrão hiper-radiante não-específico correspondente às áreas musculares dolorosas clássicas, devido à hipertonia muscular local; diferente dos pontos-gatilhos miofasciais que têm imagem térmica bem regular, elipsóide e com contornos bem definidos. O infravermelho pode ser método diagnóstico auxiliar na documentação e acompanhamento da fibromialgia (83)(84)(85) . Também foi observado que pacientes fibromiálgicos apresentam disfunção do sistema neurovegetativo simpático.…”
Section: Fibromialgiaunclassified